Quercetin as an Emerging Anti-Melanoma Agent: A Four-Focus Area Therapeutic Development Strategy - Harris, Zoey; Donovan, Micah G.; Branco, Gisele Morais; Limesand, Kirsten H.; Burd, Randy (Frontiers in Nutrition, 2016)
Replacing current refractory treatments for melanoma with new prevention and therapeutic approaches is crucial in order to successfully treat this aggressive cancer form. Melanoma develops from neural crest cells, which express tyrosinase -- a key enzyme in the pigmentation pathway. The tyrosinase enzyme is highly active in melanoma cells and metabolizes polyphenolic compounds; tyrosinase expression thus makes a feasible a target for polyphenol-based therapies. For example, quercetin (3,3′,4′,5,7-pentahydroxyflavone) is a highly ubiquitous and well-classified dietary polyphenol found in various fruits, vegetables and other plant products including onions, broccoli, kale, oranges, blueberries, apples, and tea. Quercetin has demonstrated anti-proliferative and pro-apoptotic activity in various cancer cell types. Quercetin is readily metabolized by tyrosinase into various compounds that promote anti-cancer activity; additionally, given that tyrosinase expression increases during tumorigenesis, and its activity is associated with pigmentation changes in both early- and late-stage melanocytic lesions, it suggests that quercetin can be used to target melanoma. In this review we explore the potential of Quercetin as an anti-melanoma agent utilizing and extrapolating on evidence from previous in vitro studies in various human malignant cell lines and propose a “four-focus area strategy” to develop quercetin as a targeted anti-melanoma compound for use as either a preventative or therapeutic agent. The four areas of focus include utilizing quercetin to i) modulate cellular bioreduction potential and associated signaling cascades, ii) affect transcription of relevant genes, iii) regulate epigenetic processes, and iv) develop effective combination therapies and delivery modalities/protocols. In general, quercetin could be used to exploit tyrosinase activity to prevent, and/or treat, melanoma with minimal additional side effects.